MENARASIKAN KISAH-KISAH AL-QUR’AN DALAM RUANG HISTORIS: (Studi Pemikiran Karel Steenbrink dalam The Jesus Verse of The Qur'an) - Ahmad Tri Muslim HD (Institut Agama Islam Negeri (IAIN) Keiri, 2019)
The logical consequence of the revelation pattern which was talked in the books of Qur’anic studies is that revelation (in this case al-Qur’an) seeks dialogue with the social-political dynamic of the Arab community. This thesis requires an understanding of the Qur’an depart from historical study of the verse where spesifically time and place of the verse was revealed. This model of interpretation has been aplied by Muslim scholars to a number of verses for getting a holistic meaning, but still not in the verses of the story. The accentuation of Muslim scholar interpretation tends to jump over one stage then give moral legitimation. By that, Karel Streenbrink initiated the importance of historical analysis/historical explanation of the Qur’anic naratives. This study will discuss the patterns of interpretation and aplication of the theory of Karel Streenbrink in Jesus Verse of the Qur’an. Steenbrink’s explanation to the story of the Qur’an, specially the story of Isa in the Qur’an, indicates the compatibility between the central theme of the story and the situation of da’wah Muhammad. Therefore the interpretation of the verses of the stories must be placed in a historical framework to see the social-psychological impact of the Qur’anic stories on Muhammad and his ummah.